Journal of Molecular Neuroscience - Gozes, Illana; SpringerLink (Online service) (New York : Springer US : Imprint: Humana Press.)
The Journal of Molecular Neuroscience is committed to the rapid publication of original findings that increase our understanding of the molecular structure, function, and development of the nervous system. The criteria for acceptance of manuscripts will be scientific excellence, originality, and relevance to the field of molecular neuroscience. Manuscripts with clinical relevance are especially encouraged since the journal seeks to provide a means for accelerating the progression of basic research findings toward clinical utilization. All experiments described in the Journal of Molecular Neuroscience that involve the use of animal or human subjects must have been approved by the appropriate institutional review committee and conform to accepted ethical standards.
Keywords: Neurosciences; Neurochemistry; Neurology; Proteomics; Cell biology; Neurosciences; Neurochemistry; Cell Biology; Proteomics; Neurology